2022-RA-675-ESGO Awareness, knowledge and attitudes on primary and secondary prevention of cervical cancer: a survey study. (20th October 2022) - Pergialiotis, Vasilios; Papageorgiou, Dimitrios; Douligeris, Athanasios; Mortaki, Anastasia; Thomakos, Nikolaos; Rodolakis, Alexandros; Haidopoulos, Dimitrios
Abstract : Introduction/Background: Human papillomavirus (HPV) is the most common sexually transmitted infection leading to a significant number of benign, premalignant, and malignant lesions. The aim of the present study is to evaluate the existing knowledge of a portion of the Greek population about prevention, screening, and HPV vaccination. Methodology: The survey was designed in Google forms and distributed through social media between June 2021 and December 2021 in men and women aged >16 years old that were able to read and comprehend read language. The questionnaire was pre-tested in a group of 50 obstetrics and gynecology residents. Overall, the survey included 24 questions relevant to the prevalence and pathophysiology of HPV infection, 5 questions that aimed to evaluate knowledge related to the existence of HPV testing and 9 questions that evaluated knowledge related to the existence and efficacy of HPV vaccination. Logistic regression analysis was performed to evaluate individual characteristics that predisposed participants to respond in the lowest quartile of correct answers following exclusion of questions that were considered redundant in the results of the Rasch analysis as explained later. Rasch analysis was performed to evaluate the reliability and validity of the questionnaire. Results: Overall, 2, 685 answers were received within a period of 6 months. Person reliability index was evaluated as high in both men (reliability 92.2%) and women (85.2%), indicating that both were able to correctly interpret questions and answer them. Several factors affected the rates of correct responses, including male sex, unenployed status and having a lower than average income. Conclusion: Our study suggests that although awareness of the existence of HPV infection is high in the general population perception of the pathophysiology of the disease and preventive measures remains limited, particularly among men and participants with low socioeconomic profile.